2014
DOI: 10.1186/1556-276x-9-599
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric hybrid plasmonic waveguides with centimeter-scale propagation length under subwavelength confinement for photonic components

Abstract: An asymmetric hybrid plasmonic metal-wire waveguide is proposed by combining the advantages of symmetric and hybrid plasmonic modes. The idea of asymmetric structure eliminates the adverse effect of a substrate and enhances the optical performance of the waveguide. The guiding properties of the proposed waveguide are intensively investigated using the finite elements method. The results exhibit a quite long propagation length of 2.69 cm with subwavelength confinement. More importantly, an extremely large figur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Currently, various hybrid nanostructures and materials are used to design solar cells [1 - 3], nanolasers [4 - 6], photonic switches [7,8], optical tweezers [9] and sensors [10 - 11]. Composite materials are applied in optical nanowaveguides with metal coating [12 - 15], hybrid plasmonic waveguides [16,17], and tapered metal-coated near-field optical probes with dielectric [18 - 22] and semiconductor [23 - 26] cores, which make it possible to form nanoscalelocalised light fields.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, various hybrid nanostructures and materials are used to design solar cells [1 - 3], nanolasers [4 - 6], photonic switches [7,8], optical tweezers [9] and sensors [10 - 11]. Composite materials are applied in optical nanowaveguides with metal coating [12 - 15], hybrid plasmonic waveguides [16,17], and tapered metal-coated near-field optical probes with dielectric [18 - 22] and semiconductor [23 - 26] cores, which make it possible to form nanoscalelocalised light fields.…”
Section: Introductionmentioning
confidence: 99%
“…SPs are optically induced oscillations of the free electrons at the surface of a metal and can confine and propagate electromagnetic energy far beyond the diffraction limit for electromagnetic waves in dielectric media [ 1 , 2 ]. This could lead to miniaturized photonic components with dimensions scale much smaller than those currently achieved [ 3 , 4 ], such as plasmonic waveguides [ 5 - 8 ] and plasmonic nanolasers [ 9 , 10 ]. Due to the susceptibility of SPs to surrounding dielectric, SPs and surface plasmon resonance (SPR) exhibit excellent properties for sensing applications [ 11 - 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The coherent free electron excitations (i.e., surface plasmon resonances, SPRs) which exist at the metal/dielectric interfaces are normally generated by illuminating light to metallic or metallic-dielectric hybrid structures. As yet, various plasmon-assisted optical components have been conceived and experimentally demonstrated, including waveguides [13][14][15][16][17][18][19], photon sorters [20][21][22], absorbers [23][24][25], color filters [26][27][28], and switches [29,30]. SPR based optical sensors are another important research field since they have found numerous useful applications in detecting and characterizing chemical and biological molecules.…”
Section: Introductionmentioning
confidence: 99%